Dari Sawah ke Meja Makan: Kajian Disparitas Harga Beras dan Tantangan Ketahanan Pangan di Jawa Tengah - Kurnia, Kristian Dwi; Setiadi, Bara Muhammad; Akbar, Faoza (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
This study examines rice price disparities and their implications for food security across 35 regencies and cities in Central Java, Indonesia. Using 2023 household-level data from Statistics Indonesia, the analysis applies the Gini index and concentration curve to measure spatial price inequality, and employs Ordinary Least Squares (OLS) and Three-Stage Least Squares (3SLS) regressions to analyze factors associated with rice price dynamics in the short and long term, respectively. The results reveal substantial price differences of up to IDR 5,000 per kilogram between urban consumer centers such as Surakarta City and rural production areas such as Kebumen Regency. Urban areas tend to face higher prices, which may be associated with relatively inelastic demand and constraints in supply chain coordination, while rural producers often experience low-value cycles despite abundant production. Short-term interventions, including cash assistance programs, are associated with temporary price reductions; however, 3SLS estimates indicate that these effects are not consistently sustained in the long run in the absence of structural improvements. The expansion of rural credit through village banking institutions indicates improved access to finance but does not significantly reduce long-term rice prices, reflecting persistent post-harvest and distribution inefficiencies. Overall, the findings suggest that rice price disparities are not merely temporary market fluctuations but reflect deeper structural and institutional imbalances. This study recommends integrating financial access with supply chain investment, strengthening regional price monitoring, and coordinating social protection policies to support equitable and sustainable rice availability.